Stroke prevention for non-valvular atrial fibrillation: how to make the right choice of directly acting oral anticoagulants? - N. N. Kryukov; E. V. Sayutina; A. M. Osadchuk; M. A. Osadchuk (Российский кардиологический журнал)
Patients with atrial fibrillation have a high risk of developing stroke and death, which requires constant anticoagulant support. In this regard, the physician faces the difficult task of selecting the appropriate oral anticoagulant for patient with individual risk factors and comorbidities. Currently, three non-vitamin K antagonist oral anticoagulants or directly acting oral anticoagulants have been registered in the Russia, which in large randomized clinical trials (RCTs) were compared with warfarin in the prevention of stroke and systemic embolism. The present article analyzes the data of RCTs, postmarketing studies of oral anticoagulants, and presents groups of patients for whom these drugs are preferred. The choice of oral anticoagulants for the prevention of stroke in the following subgroups of patients with atrial fibrillation is discussed: patients with one stroke risk factor (CHA2DS2VASc1 in men or 2 in women), patients of different age groups, patients with concomitant coronary artery disease/acute coronary syndrome, a history of stroke, patients with chronic kidney disease, patients with a high risk of gastrointestinal bleeding, and a group of patients with concomitant arterial hypertension and chronic heart failure. We compared the efficacy and safety of oral non-vitamin K antagonist oral anticoagulants or directly acting oral anticoagulants with vitamin K antagonists in patients with non-valvular atrial fibrillation.